Cartografia das unidades de conservação e territórios dos povos tradicionais no Paraná - Marquiana de Freitas Vilas Boas Gomes; Emerson de Souza Gomes; Raimundo Nonato Junior (Confins)
Traditional people and communities present a symbiotic relation with the environment, territory of people existence, therefore those people significantly contribute for the environmental conservation. The Conservation Units (UCs) which are addressed to full protection and/or the use of sustainable natural resources, when overlapped to people and community territories, may trigger territorial usage conflicts. In this article, we address this problem by means of overlapped cartography of conservation units related to territories that are traditionally occupied by people and communities of Paraná Brazilian state. Here, we focus on people presence, tension points and needs of dialog. By means of a qualitative methodological approach articulated to quantitative data obtained from official regional research offices, we produced maps, tables and further, we analyzed this subject. Results show that in Parana state more than three millions of hectares are destined to UCs distributed in 125 municipalities, attached to three administrative spheres: cities, states and federal government. We observed that among 49 municipalities where we found matches between traditional communities and UCs, we discovered 22 unities of full protection and 31 of sustainable usage. However, the overlapping of UCs and territories of traditional communities exposes the coexistence between local players and politicians which have different interests regarding to the same territory, thus opening a new window of debates about the limits and rights of each one of the players.